2008
DOI: 10.1007/s00148-008-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there asymmetries in the effects of training on the conditional male wage distribution?

Abstract: Recent studies have used quantile regression (QR) techniques to estimate the impact of education on the location, scale and shape of the conditional wage distribution. We conduct a similar investigation of the role of work-related training. We utilise both ordinary least squares and QR techniques to estimate associations between work-related training and wages for private sector men in ten European Union countries. For the majority of countries, the association between training and hourly wages varies little a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
13
2
Order By: Relevance
“…Using decomposition analysis they find training is positively associated with wage dispersion. However, this finding is in contrast with finding by Arulampalam et al (2010) who find the association between training and hourly wages varies little across the conditional wage distribution for the majority of countries in EU. Of course, their sample is different since they focus only on private sector men and so our estimates are not comparable.…”
Section: Quantile Regression Estimatescontrasting
confidence: 99%
See 3 more Smart Citations
“…Using decomposition analysis they find training is positively associated with wage dispersion. However, this finding is in contrast with finding by Arulampalam et al (2010) who find the association between training and hourly wages varies little across the conditional wage distribution for the majority of countries in EU. Of course, their sample is different since they focus only on private sector men and so our estimates are not comparable.…”
Section: Quantile Regression Estimatescontrasting
confidence: 99%
“…Since the years of schooling is significantly related to monthly wage at each quantile and the QR estimates do not differ significantly across all quantiles, it can be concluded that years of schooling only affects the location of the conditional wage distribution. The findings are not consistent with previous findings by Arulampalam et al (2010), Budría and Pereira (2004) in which education is associated with increased dispersion of the conditional wage distribution. The observed negative sign of the QR estimates of work experiencesquared, EXP2 in all the five quantiles indicates that the monthly wage increases at a decreasing rate as years of work experience increase.…”
Section: Quantile Regression Estimatescontrasting
confidence: 99%
See 2 more Smart Citations
“…Dearden, Reed andVan Reenen, 2000 andArulampalam, Booth andBryan, 2004). Therefore, heterogeneity in training returns cannot only be explained by differences in productivity effects of training, but also by differences in individual, firm, and job characteristics which relate to the bargaining power of employer and employee.…”
Section: Background Discussionmentioning
confidence: 99%